THE USE OF ARTIFICIAL INTELLIGENCE (AI) TO IMPROVE MARKETING CAMPAIGN EFFECTIVENESS - Alhabshy, Musa Alkadhim (Universitas Dharma Wacana, 2025)
Digital transformation has drastically changed the marketing landscape, with Artificial Intelligence (AI) playing a central role in redefining more effective and adaptive marketing campaign strategies. This study aims to analyze the forms, implementation strategies, and impact of AI use on increasing marketing campaign effectiveness across various industry sectors.Through a mixed methods approach combining quantitative and qualitative data, this study found that AI significantly improves market segmentation accuracy, enhances message personalization, strengthens customer engagement, and optimizes campaign budget and timeline management. Technologies such as machine learning, chatbots, and predictive analytics have been shown to accelerate the decision-making process and drive more measurable and responsive campaigns.However, the success of AI integration is also influenced by the readiness of digital infrastructure, human resource competency, and compliance with data protection regulations and ethics. The results of this study demonstrate that AI is not merely a technological tool, but a strategic instrument in building smarter, more efficient, and more consumer-oriented marketing communications. These findings are important for companies, particularly SMEs, to understand the potential and challenges of AI in designing impactful campaigns within a dynamic digital marketing ecosystem.